Total heterotopic ossification of the thyroid: Exceptional case (JOURNAL OF THE FACULTY OF MEDICAL SCIENCES, 2023)
Heterotopic ossification, that is, calcifications in tissues that do not normally calcify or ossify; it occurs in previously altered or pathological tissues such as ganglia, nodules, scars, etc., with normal serum calcium levels. Some ossifications or calcifications do not cause symptoms, and their clinical manifestation is usually more aesthetic because it is a chronic problem.They are detected in a first instance by radiography where some radiopaque image is detected on soft tissue, the contracted tomography is the exam of choice (dense radio image).The present case is about a 58-year-old female patient, who presents with a hard mass that covers the entire neck contour that limits movement and causes slight pain to flexion and laterality.
Keywords: ossification; heterotopic; thyroid